(untitled) (CIPEEX, 2024)
Forensic radiology plays a crucial role in both anthropology and archeology, offering non-invasive tools for the analysis of human remains and artifacts. In forensic anthropology, radiology helps identify biological characteristics of individuals, such as age, sex and ancestry. This is critical in crime or disaster investigations, where accurate identification can be challenging. In archaeology, radiology allows you to examine graves and artifacts without damaging them. Techniques such as computed tomography (CT) can reveal internal details of bones or objects, providing valuable information about cultural and burial practices. Additionally, radiography can help detect pathological changes in bones, offering insights into the health and living conditions of past populations. These technologies contribute to a deeper understanding of the human past, uniting science and history in a fascinating way. There are several radiological imaging techniques that are fundamental in the study of mummies and skeletons. Radiography, Computed Tomography (CT), Resonance and Ultrasonography.These techniques not only help in the identification and analysis of human remains, but also offer insights into the cultural practices and living conditions of ancient populations. Forensic Radiology has contributed significantly to the understanding of burial practices and health conditions of ancient populations . There are several fascinating discoveries in studies of Egyptian mummies and prehistoric skeletons that have been made using radiological techniques such as the Mummy of Ramesses II: Radiological studies have shown signs of arthritis and heart disease in Ramesses II, as well as evidence of possible cancer . Tomography allowed a detailed analysis of the state of bones and tissues, offering a clearer view of the life and health of the pharaohs. The application of forensic radiology in archaeological contexts brings to light a series of challenges and ethical considerations that are fundamental to ensuring respect for past cultures and individuals.